Improved Canadian seismic provisions for steel braced frames in heavy industrial structures. (February 2019) - Brunet, Frédéric; Tremblay, Robert; Richard, Julien; Lasby, Mark
Abstract: The seismic provisions of the Canadian CSA S16-14 standard for steel structures for heavy industrial steel structures are reviewed and applied for a 65.4 m tall concentrically braced frames (CBFs) for an industrial application in Vancouver, BC. Two approaches are examined: a capacity design method in accordance with CSA S16 Annex M and a simpler, non-capacity design approach for the structures of the Conventional Construction (Type CC) category. Nonlinear response history analyses are performed to examine and compare the seismic response of the structures. Modifications are proposed to mobilize higher brace inelastic response, mitigate storey drift concentrations, and ensure that the columns can safely resist the seismic induced axial and flexural demands. The modified provisions are validated for additional structures having heights varying from 43 to 80 m and two different vertical distribution of the seismic weights. The robustness of the structures against excessive storey drifts and column buckling limit states is verified through incremental dynamic analysis. Both Annex M and Type CC design approaches, as modified in this study, represent two practical options to achieve cost-effective designs resulting in satisfactory seismic response. Three-dimensional nonlinear response history analysis is used to compare the 100%–100% and 100%–30% combination rules to predict the axial load demand on columns part of two orthogonal CBFs. For the structure studied, the results showed that the latter would give more realistic force estimates. Highlights: CSA S16 seismic provisions for tall industrial steel braced frames are reviewed. Capacity and non-capacity design methods are applied and compared for sample frames. Nonlinear response history analyses are performed to assess the seismic responses. Modifications to design provisions are proposed to improve the frame responses. Seismic axial loads in columns part of two orthogonal braced frames are evaluated.